Implementation a Real Monitoring Information System for English Language Skill - Mike Amelia; Fitri Handayani (English Language Education Department, Universitas Majalengka, 2025)
This study aimed to implement, and evaluate a real-time monitoring information system to enhance the development of English language skills among students. Traditional methods of language learning often lack immediate feedback and individualized tracking, which are critical for skill improvement. To address this gap, a web-based system was developed to monitor student performance in listening, speaking, reading, and writing, providing real-time analytics to both students and teacher.The research employed a design and development approach using a mixed-methods evaluation. Fifty students and five English teachers at SDN Pasir Jengkol II Karawang participated in this reasearch. Quantitative data from system, and pre-tests and post tests were analyzed alongside qualitative feedback from surveys and interviews. Results indicated significant improvements in student performance across all skill areas, with an average increase of over 12% in post-test scores. User feedback revealed high levels of satisfaction with the system’s usability and usefulness, and indicating excellent usability. In conclusion, the real-time monitoring system effectively supported English language learning and instructional practices by providing timely feedback, increasing student motivation, and enabling data-driven decision-making. The findings suggest that such systems have strong potential for broader implementation in language education.